Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01629
|View full text |Cite
|
Sign up to set email alerts
|

Superficieibacter electus gen. nov., sp. nov., an Extended-Spectrum β-Lactamase Possessing Member of the Enterobacteriaceae Family, Isolated From Intensive Care Unit Surfaces

Abstract: Two Gram-negative bacilli strains, designated BP-1(T) and BP-2, were recovered from two different Intensive Care Unit surfaces during a longitudinal survey in Pakistan. Both strains were unidentified using the bioMerieux VITEK MS IVD v2.3.3 and Bruker BioTyper MALDI-TOF mass spectrometry platforms. To more precisely determine the taxonomic identity of BP-1(T) and BP-2, we employed a biochemical and phylogenomic approach. The 16S rRNA gene sequence of strain BP-1(T) had the highest identity to Citrobacter farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We found 12 instances where genomes did not have >95% ANI with the identified MALDI-TOF MS hit or the most closely related genomes as determined by 16S rRNA gene sequence in the EzBioCloud database, indicating that these are putative novel genomospecies. A separate investigation found that 2/7 of the isolates unidentified by MALDI-TOF MS are a new genus of multidrug-resistant Enterobacteriaceae , termed Superficieibacter electus 31 . The previously unreported genomospecies come from the Caulobacteriacae , Xanthomonadaceae , and Enterobacteriaceae families, and five of the proposed new genomospecies are Pseudomonadaceae .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 12 instances where genomes did not have >95% ANI with the identified MALDI-TOF MS hit or the most closely related genomes as determined by 16S rRNA gene sequence in the EzBioCloud database, indicating that these are putative novel genomospecies. A separate investigation found that 2/7 of the isolates unidentified by MALDI-TOF MS are a new genus of multidrug-resistant Enterobacteriaceae , termed Superficieibacter electus 31 . The previously unreported genomospecies come from the Caulobacteriacae , Xanthomonadaceae , and Enterobacteriaceae families, and five of the proposed new genomospecies are Pseudomonadaceae .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to commonly recognized HAI causing bacteria, we found many potentially opportunistic pathogens and novel genomospecies from commonly pathogenic genera ( Pseudomonas , Stenotrophomonas , Brevundimonas ). The first novel genomospecies from this collection to be fully characterized, S. electus , is a new genus of Enterobacteriaceae that harbored extended spectrum β-lactamases and was multidrug resistant 31 . A previous taxonomic investigation determined that species from another novel genus of Enterobacteriaceae , Pseudocitrobacter faecalis and Pseudocitrobacter anthropi , harbored bla NDM-1 carbapenemases, and were identified in fecal samples from patients at hospitals in Pakistan 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of WGS and phylogenomic methods in taxonomic resolution of the family Enterobacteriaceae has been previously demonstrated (Adeolu et al, 2016; Alnajar and Gupta, 2017). Recently, a novel genus was proposed based on phenotypic and phylogenomic analysis (not validated yet) (Potter et al, 2018). We determined the genome sequence of strain CCUG 66741 T in order to resolve the taxonomic identity of the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation, sequencing, and sequence analysis were performed as described previously (32) using 12 World Health Organization (WHO) reference genomes (18) (Table S2). Genomic DNA was obtained from pure N.…”
Section: Methodsmentioning
confidence: 99%